Features of geostationary satellite navigation by time difference of arrival method - Kolodchak, Ivan; Zahakaylo, Volodymyr; Luts, Volodymyr (Видавництво Львівської політехніки, 2010)
Features of the geostationary satellite navigation (definition of coordinates and velocities) by multiposition radio passive systems with the use of the time difference of arrival method have been considered. It is shown that in this case the most expedient way of solving the system of nonlinear equations for definition of coordinates of the satellite is linearization of the system with the successive iterative approximation to a preset criterion of accuracy. The full satellite state vector is formed by the extended Kalman filter.
Keywords: geostationary satellite; time difference of arrival method; state vector